1988
DOI: 10.3109/17453678809149340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sterilization on osteoinduction Comparison of five methods in demineralized rat bone

Abstract: The aim of this study was to find a safe, effective sterilization method that does not destroy the bone-inductive capacity of demineralized bone implants. Five sterilizing agents were tested in rats. Implants procured and processed under sterile conditions served as controls. New bone formation was evaluated by determining dry weight, calcium content, and Sr-85 incorporation of the induced ossicles. Glutaraldehyde solution, formaldehyde gas, and ethylene oxide destroyed almost all the bone-inductive capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0
5

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 12 publications
1
74
0
5
Order By: Relevance
“…Heat treatment greater than 60°C reduces the strength [41,42,45,71,72] and impairs osteoinductivity [44]. Chemical treatments such as ethylene oxide and hydrogen peroxide also are harmful to osteoinductivity [8,15,24,25,54,56]. Gamma radiation sterilization is the current standard given its convenience and efficacy in achieving sterility and the response toward HIV and hepatitis C [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment greater than 60°C reduces the strength [41,42,45,71,72] and impairs osteoinductivity [44]. Chemical treatments such as ethylene oxide and hydrogen peroxide also are harmful to osteoinductivity [8,15,24,25,54,56]. Gamma radiation sterilization is the current standard given its convenience and efficacy in achieving sterility and the response toward HIV and hepatitis C [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, irradiation has been found to inhibit (Buring and Urist 1967) or only partially destroy (Munting et al 1988, Schwarz et al 1988, Ijiri et al 1994, Zhang et al 1997) the osteoinductive capacity. In others, no effect of irradiation on the osteoinductive capacity has been found (Wientroub and Reddi 1988, Andriano et al 2000, Ripamonti et al 2000, Pekkarinen et al 2005.…”
Section: Histomorphometrymentioning
confidence: 99%
“…These proteins may be released during the resorptive phase of bone graft incorporation, and can have a profound effect on bone cell physiology. Although studies have been performed to determine the effect of irradiation on BMPs (Munting et al 1988, Wientroub and Reddi 1988, Dziedzic-Goclawska et al 1991, Ijiri et al 1994, Andriano et al 2000, Ripamonti et al 2000, Pekkarinen et al 2005, the effect of irradiation on the incorporation process of morselized bone chips remains unclear. We studied the effects of steri-lization by gamma irradiation on the incorporation of impacted morselized allografts.…”
mentioning
confidence: 99%
“…Authors disagree on whether or not ethylene oxide sterilization impairs osteoinduction (Munting et al 1988, Aspenberg et al 1990, Urist 1968, Kohler and Kreicbergs 1987, Zislis et al 1989, Moore et al 1990). …”
mentioning
confidence: 99%
“…It has been suggested that demineralized bone as intact segments (Tuli and Singh 1978, Einhom 1984, Delloye et al 1985, Munting et al 1988 or particles (Iwata et al 1981, Bolander and Baslian 1986, Gepstein et al 1987, Kohler and Kreicbergs 1987 might improve the healing of diaphyseal segmental defects. However, unless a standard bone graft is compared with identically processed, but also demineralized bone, conclusions are unreliable.…”
mentioning
confidence: 99%